Overcoming gender inequalities through technology integration - Wilson, Joseph 1972-; Gapsiso, Nuhu Diraso (Advances in human and social aspects of technology (AHSAT) book series, 2016)
"This book is a critical source for understanding the role of technology adoption within female empowerment and equality in developing nations and beyond, examining the strategies applicable to the use of technology among women in developing as well as developed countries in which they have access to ICTs"...